Cross-Cultural Adaptation, Reliability, and Validity of a Brazilian of Short Version of the Posttraumatic Diagnostic Scale - de Faria Cardoso, Cláudia; Ohe, Natalia Tiemi; Taba, Vera Lúcia; Paiva, Tamyres Tomaz; Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida (Frontiers in Psychology, 2021)
Background: A short version of the Posttraumatic Diagnostic Scale (PDS) comprising only re-experiencing symptom items has been recently validated on Japanese adults. This short-version-PDS had good psychometric properties among Japanese adults with and without posttraumatic stress disorder (PTSD). The aim of this study was to translate and culturally validate the short-version-PDS for the Brazilian sociolinguistic context. Methods: A translation of the short-version-PDS was performed based on established guidelines. The translation and cross-cultural adaptation of the short-version-PDS included forward and back-translation by a Japanese Brazilian researcher and a certified translator; synthesis was achieved by consensus, backward translation, pilot test, and finalization. Content validity coefficient (CVC) was used to assess quality of adaptation. Internal consistency was calculated using Cronbach's alpha coefficient. Spearman correlations were between the short-version-PDS and DSM-5 (Diagnostic and Statistical Manual of Mental Disorders) PTSD scale, and a receiver operating characteristic (ROC) curve was used to determine the best cut-off values for the short-version-PDS. Results: The short-version-PDS was well accepted by all subjects, none of the questions were experienced as inappropriate, and all questions of the 3 items were judged important. Item 1 presented CVCt = 0.92; item 2 had a CVCt = 0.87 and item 3 had a CVCt = 0.95. The internal consistency of the final version as measured by Cronbach’s alpha was 0.78. The short-version-PDS scale correlated positively with the DSM-5 scale with a Spearman rho of 0.64 (95%CI [0.4-0.8], p < 0.001). The receiver operating characteristic (ROC) curve value was 0.97 (95%CI [0.9-1.0], p < 0.001). The cut-off score for a maximum Youden Index of 0.8 to distinguish moderate from severe from slight PTSD was > 31.0 with sensitivity and specificity are 86.4% and 93.5%, respectively. Conclusions: This Brazilian Portuguese version of the short-version-PDS had good psychometric properties among Brazilian adults with and without PTSD. Transferability and generalizability of the cut-off scores should be further analyzed.